Pengaruh Customer Experience Dan Citra Merek Terhadap Loyalitas Pelanggan Di PT. Pegadaian Cabang Medan - Suhartono, Andika; Akbar, Aswin (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims the relationship between Customer Experience (X1) and Brand Image (X2) on customer loyalty (Y) at PT Pegadaian Medan Branch. Taking into account the dynamic changes in the financial services industry and the evolution of consumer preferences, this study aims to understand how customer experience and brand image influence customer loyalty decisions. The research sample was 165 people through data analysis from February to May 2024, this study highlights the importance of a satisfying customer experience and a positive brand image in maintaining and increasing customer loyalty. Sampling using random sampling. Data analysis using Multiple Regression test, hypothesis testing using the coefficient of determination test (R2), partial test (t test), and simultaneous test (F test) while data processing using SPSS 28. The results showed that from the coefficient of determination test (R2) the Customer Experience and Brand Image variables were able to explain their existence to customer loyalty, besides that partially Customer Experience has a significant effect on customer loyalty and Brand Image has a significant effect on customer loyalty and simultaneously Customer Experience and Brand Image have a significant effect on customer loyalty.